Regenerative Therapy Using Blood-Derived Stem Cells - Allan, David S.; Strunk, Dirk.; SpringerLink (Online service) (Totowa, NJ : Humana Press, 2012)
Regenerative medicine is the emerging science of how we can support our body to repair itself and encompasses innovative strategies to facilitate recovery after organ injury. Several types of blood-derived stem cells can be easily procured and have the potential to facilitate this repair process. Our understanding of the various cell types and precise mechanisms of repair are evolving quickly. In this book, several key types of blood-derived stem cells that participate in the repair of organ damage are reviewed and specific examples of how stem cells may improve heart damage and neurological injury are addressed. Practical approaches to preparing cellular products and regulatory issues that will govern translational studies in patients are also covered. Regenerative Therapy Using Blood-Derived Stem Cells is a timely publication of a fast-moving field that will stimulate further research and enquiry into the promising field of regenerative medicine.
Undertaking Regenerative Medicine Studies with Blood Stem Cells -- Defining Endothelial Progenitor Cells -- Blood-Derived ALDHhi Cells in Tissue Repair -- Blood Derived Mesenchymal Stem Cells and Tissue Repair -- Animal Protein-Free Expansion of Human Mesenchymal Stem / Progenitor Cells -- Defining Hierarchies of USSC and MSC in Cord Blood -- iPS Cells from Blood-Derived Cells -- Endothelial Progenitors and Repair of Cardiovascular Disease -- Bone Marrow-Derived Cells as Treatment Vehicles in the Central Nervous System -- Regenerative Potential of Blood Stem Cell Products Used in Hematopoietic Stem Cell Transplantation -- Concepts to Facilitate Umbilical Cord Blood Transplantation -- Cord Blood Banking for Regenerative Therapy -- Regulatory Questions in the Development of Blood Stem Cell Products for Regenerative Therapy -- Cell Therapy Regulations from a European Perspective -- EBMT Registry of Non-Hematopoietic Stem Cells and Regenerative Therapy (Cellular and Engineered Tissue Therapies in Europe).
Keywords: Life sciences; Hematology; Cytology; Stem cells; Life Sciences; Stem Cells; Cell Biology; Hematology